Best Practices as to How to Support Investment in Intangible Assets - Alexander Ebner; Fabian Bocek (WWWforEurope, 2015)
Intangible investment is an indispensable factor in the projected socio-ecological transition towards a new European path of economic growth. Its concern with knowledge-based intangible assets highlights the innovation-driven formation of a knowledge-based economy, which is at the heart of current EU strategies for the promotion of sustainable growth. The policy report will summarise best practices of supporting investments in intangible assets in the EU member states at the level of firms, industries and countries as a whole. In proceeding with this work, the policy report will draw on insights that were developed in preceding FP7 projects, in particular COINVEST. This allows for an understanding of intangible investment as investment in intangible assets that provide firm-specific flows of knowledge services. These involve both formal and tacit knowledge in diverse areas such as firm-funded investment in R&D, education and training, software and databases as well as design and branding, accompanied by mechanisms of inter-firm cooperation in the management of knowledge assets. The diverse strategies and policies in support of intangible investment across the EU are going to be assessed on the basis of available cases and data about best practices. The resulting policy report is set to sort out those strategies and policies that provide the most effective support of intangible investment in the formation of a socio-ecologically sustainble knowledge-based economy.
Keywords: D22; D83; M19; 330; Economic growth path; High road strategy; Innovation; Intangible assets; Social capital as growth driver; Socio-ecological transition